2000
DOI: 10.1111/j.1540-8167.2000.tb00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Remodeling of Kv4.3 Potassium Channels in Human Atrial Fibrillation

Abstract: Chronic AF in humans reduces Ito by transcriptional down-regulation of the Kv4.3 potassium channel. Altered gene expression is an important component of the electrical remodeling process and may contribute to repolarization abnormalities in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 26 publications
5
53
1
3
Order By: Relevance
“…In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003). Similar alterations to those given by Courtemanche et al (1999) have been observed in other experiments as well (Dobrev and Ravens, 2003), including substantial reductions in I Ca,L (Bosch et al, 1999;Van Wagoner et al, 1999;Skasa et al, 2001;Workman et al, 2001) and I to (Van Wagoner et al, 1997;Bosch et al, 1999;Brandt et al, 2000;Grammer et al, 2000;Workman et al, 2001). The reduction in I Kur proposed by Courtemanche et al (1999) has been found in some studies (Van Wagoner et al, 1997;Brandt et al, 2000) but not in others (Grammer et al, 2000;Workman et al, 2001).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 83%
“…In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003). Similar alterations to those given by Courtemanche et al (1999) have been observed in other experiments as well (Dobrev and Ravens, 2003), including substantial reductions in I Ca,L (Bosch et al, 1999;Van Wagoner et al, 1999;Skasa et al, 2001;Workman et al, 2001) and I to (Van Wagoner et al, 1997;Bosch et al, 1999;Brandt et al, 2000;Grammer et al, 2000;Workman et al, 2001). The reduction in I Kur proposed by Courtemanche et al (1999) has been found in some studies (Van Wagoner et al, 1997;Brandt et al, 2000) but not in others (Grammer et al, 2000;Workman et al, 2001).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 83%
“…Of note, other studies using larger species have reported good correlations between protein and gene expression of the Kv4.3 potassium channel (encoded by Kcnd3; Figure 7A), and down-regulation of this channel was associated with AF in humans and dogs. [51][52][53][54] PI3K(p110␣) has also been reported to differentially regulate metabolism genes in ventricular tissue. 55 Further studies are required to examine the functional consequence of these alterations in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…11 In experimental reports from animal models in which tachycardia lasted several hours to several months, there was down-regulation of the L-type calcium current (IcaL) 12,13 associated with excessive intracellular calcium loading, and down-regulation in the ultrarapid delayed rectifier potassium current (Ikur), 14 transient outward potassium current (Ito), 13 sodium current (INa) 15 and slow-type delayed rectifier potassium current (Iks) 16 as an up-regulation of ion channels. In human atrial muscle that has been converted to permanent AF, down-regulation of ion channels such as the L-type calcium current (IcaL) 17 and transient outward potassium current (Ito), 18 and up-regulation of the inward potassium current (Ikl) and acetylcholine-activated potassium current (IKach) 17 have been reported, whereas neither the ultrarapid delayed rectifier potassium current (Ikur) 18 nor rapid delayed rectifier potassium current (Ikr) 19 showed any changes. Those changes in the ion channels result in a shortened effective refractory period of atrial muscle and shortened excitable wave lengths according to the reduction of conduction velocity.…”
Section: Discussionmentioning
confidence: 99%